2022
DOI: 10.1007/s12094-022-02784-0
|View full text |Cite
|
Sign up to set email alerts
|

Review of imaging techniques for evaluating morphological and functional responses to the treatment of bone metastases in prostate and breast cancer

Abstract: Bone metastases are very common complications associated with certain types of cancers that frequently negatively impact the quality of life and functional status of patients; thus, early detection is necessary for the implementation of immediate therapeutic measures to reduce the risk of skeletal complications and improve survival and quality of life. There is no consensus or universal standard approach for the detection of bone metastases in cancer patients based on imaging. Endorsed by the Spanish Society o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 119 publications
0
18
0
1
Order By: Relevance
“…Four imaging biomarkers were computed from the manual and automatic segmentations, and these produced promising results for predicting the treatment response. Improved results can be obtained using multimodal imaging modalities like PET/CT [ 36 ]. Arends et al [ 89 ] showed that automatic vertebral body delineation using CNN was of high quality, which can save time in a clinical radiotherapy workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Four imaging biomarkers were computed from the manual and automatic segmentations, and these produced promising results for predicting the treatment response. Improved results can be obtained using multimodal imaging modalities like PET/CT [ 36 ]. Arends et al [ 89 ] showed that automatic vertebral body delineation using CNN was of high quality, which can save time in a clinical radiotherapy workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear imaging can efficiently fill these gaps by capturing molecular events with high sensitivity [ 12 ]. While, here we are covering molecular PET imaging and skeletal scintigraphy ( Table 1 ); we acknowledge additional functional and anatomical modalities such as CT and MRI that play an essential role in evaluating bone metastasis and are covered by other dedicated reviews on these respective modalities [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hematopoietic lineage in the bone marrow is responsible for pre-osteoclastogenesis and mature osteoclast is a specialized macrophage with multiple mitochondria and lysosomes for bone degradation [1]. The cell-cell fusion process of pre-osteoclasts forming a mature osteoclast has a checkpoint, the stromal cells, which have the fast and accessible explorationthat allows detection of the presence of lytic lesions (with greater than 50% destruction of the mineralized bone), blastic lesions, mixed lesions or complications, pathological fractures [12]. Metastases measuring up to 1 cm in the spongiosa of a vertebral body or in the marrow of a long bone can be missed on plain X-ray, but pathological changes in cortical bone are detectable by plain X-ray even if they are only a few millimeters wide [4].…”
Section: Discussionmentioning
confidence: 99%